Clinical challenges and patient experiences in early-onset colorectal cancer: insights from seven European countries - Marianna Vitaloni; Katell Maguet; Andi Carlan; Patricia Stack; Vincent de Jong; Ross Williams; Zorana Maravic (BMC Gastroenterology)
Abstract Background The incidence of early-onset colorectal cancer (eoCRC), defined as CRC diagnosed in individuals under 50, is rising globally. Younger patients often face diagnostic delays and receive care pathways designed for older populations. These gaps highlight the need for tailored approaches to diagnosis, treatment, and support. Objective This study aimed to explore the lived experiences and challenges of eoCRC patients across seven European countries to inform public health strategies and improve patient-centered care. Methods We conducted qualitative focus groups with 47 eoCRC patients and survivors from France, Ireland, Italy, the Netherlands, Romania, Spain, and the United Kingdom. Discussions were analyzed using a thematic approach, focusing on three stages of the patient journey: pre-diagnosis, diagnosis, and post-diagnosis. Results Participants highlighted several key challenges, including low awareness of CRC symptoms among younger populations, diagnostic delays linked to age and gender biases, and limited access to age-appropriate support services. Many participants reported significant quality-of-life (QoL) impacts related to disrupted careers, intimacy issues, and challenges managing family responsibilities during treatment. Psychological support, physiotherapy, and nutritional counseling were inconsistently available, with significant disparities across public and private healthcare systems. Conclusions The findings underscore the urgent need for targeted public health campaigns to raise awareness of eoCRC, improved training for healthcare providers to reduce diagnostic delays, and expanded access to tailored support services. Addressing these gaps is critical to mitigating the growing burden of eoCRC and improving outcomes for younger patients.